Caveolin enhances hepatocellular carcinoma cell metabolism, migration, and invasion in vitro via a hexokinase 2‐dependent mechanism. Issue 2 (24th August 2018) - Chai, Fang; Li, Yan; Liu, Keyi; Li, Qiang; Sun, Hongzhi
Abstract : The development and progression of hepatocellular carcinoma (HCC) have been associated with abnormal cellular metabolism. Gene Expression Profiling Interactive Analysis RNA sequencing data revealed caveolin‐1 (CAV‐1) and hexokinase 2 (HK2) messenger RNA (mRNA) were significantly upregulated in human HCC compared with normal tissues, and high HK2 expression was associated with significantly poorer overall survival in HCC ( p < 0.05). CAV‐1 and HK2 mRNA and protein expression were upregulated and positively correlated in 42 fresh human HCC tissues compared with tumor‐adjacent normal tissues. Overexpression of CAV‐1 or HK2 in SMMC‐7721 and HepG2 HCC cells enhanced glucose and lactate metabolism and increased cell migration and invasion in transwell assays; knocking down CAV‐1 or HK2 had the opposite effects. Overexpression of CAV‐1 increased HK2 expression; overexpression of HK2 did not affect CAV‐1 expression. Knocking down HK2 partially reversed the ability of CAV‐1 to promote cellular metabolism, invasion, and migration in HCC, indicating CAV‐1 enhances glycolysis, invasion, and metastasis in HCC cells via HK2‐dependent mechanism. Further studies of the function and relationship between CAV‐1 or HK2 expression are warranted to explore the potential of these proteins as metabolic targets for the treatment of HCC. Abstract : Caveolin‐1 (CAV‐1) increased hexokinase 2 (HK2) expression. CAV‐1 enhances glycolysis, invasion, and metastasis in hepatocellular carcinoma cells via a HK2‐dependent mechanism.